A Counselling Model for Young Women in the United Arab Emirates: Cultural Considerations - Lambert, Louise (Canadian Journal of Counselling and Psychotherapy, 2008)
Although all modalities of therapy work equally well, some models are better suited to work with specifi c populations. This article outlines a rationale for a counselling model used for female college students in the United Arab Emirates where the concept of counselling is not well known, and where the social and cultural organizations demand a more flexible and informal approach to helping. Two cases are presented using a systemic and solution-focused approach that accommodates culture, religion, and the gender and social hierarchy in this society through the use of family members and intermediaries.